Refined non-steady-state gas-liquid chromatography for accurate determination of limiting activity coefficients of volatile organic compounds in water: application to C(1)-C(5) alkanols - Dohnal, Vladimír; Ondo, Daniel (Journal of chromatography. A, Including electrophoresis and other separation methods, 2005)
This work presents a new refined method of non-steady-state gas-liquid chromatography (NSGLC) suitable for determination of limiting activity coefficients of VOCs in water. The modifications done to the original NSGLC theory address its elements (as the solvent elution rate from the column) as well as other new aspects. The experimental procedure is modified accordingly, taking advantage of current technical innovations. The refined method is used systematically to determine limiting activity coefficients (Henry's law constants, limiting relative volatilities) of isomeric C(1)-C(5) alkanols in water at 328.15K. Applied to retention data measured in this work the refined NSGLC theory gives values 15-20% higher than those from the original approach. The values obtained by the refined NSGLC method agree very well (typically within 3%) with the most reliable literature data determined by other experimental techniques, this result verifying thus the correct performance of the refined method and demonstrating an improved accuracy of the new results.
Keywords: Organic Chemicals; financování organizované; methanol; Chemistry, Physical; Chromatography, Gas; teoretické modely; Volatilization; ethanol; butanoly; Reproducibility of Results; Methanol; chemické jevy; fyzikální chemie; 1-Propanol; Butanols; Algorithms; Ethanol; Chemical Phenomena; voda; Financing, Organized; 1-propanol; reprodukovatelnost výsledků; Water; Pentanols; chromatografie plynová; pentanoly; algoritmy; organické látky; volatilizace; Models, Theoretical